Transplantation of donor lungs with pulmonary embolism – a retrospective study. (21st February 2019) - Sommer, Wiebke; Kirschner, Helmut; Ius, Fabio; Salman, Jawad; Siemeni, Thierry; Bobylev, Dmitry; Avsar, Murat; Kuehn, Christian; Greer, Mark; Gottlieb, Jens; Rahmel, Axel; Welte, Tobias; et al.
Summary: Lung transplantation from donors with fulminant pulmonary arterial embolism as a cause of death remains controversial. An analysis was performed comparing preoperative characteristics and outcomes of 25 donors with a primary diagnosis of pulmonary arterial embolism to 1085 recipients of donor lungs without pulmonary arterial embolism. No early functional impairment of donor lungs with pulmonary embolism was detectable as depicted by the incidence of primary graft dysfunction immediately after surgery ( P  = 0.66), 24 ( P  = 0.79), 48 ( P  = 0.99) and 72 h ( P  = 0.99) after transplantation. Pulmonary function testing at 1 year ( P  = 0.003) and at last outpatient control ( P  < 0.05) showed superior results in the cohort receiving lungs from donors with pulmonary embolism. Incidence of chronic lung allograft dysfunction (CLAD) showed no difference within the first year after lung transplantation, however, 5 year‐CLAD free survival was superior in recipients (70.4% vs. 55.1%, P  = 0.006) of donor lungs with pulmonary embolism. Overall survival was similar in both groups. Lungs from donors with fulminant pulmonary embolism prior to brain death can safely be used for lung transplantation without impairing postoperative outcomes. Lung function testing shows favorable midterm results in recipients of donor lungs with pulmonary embolism.